Leaders of health education in the modern school - Nowak, Paweł F. (Polish Journal of Public Health, 2012)
Introduction. Only a teacher, who enters into the role of a charismatic leadership personality may effectively pursue the process of health education in school.Aim. Knowing teachers’ views – teachers of different specialties – on the leaders in health education in Polish schools was the main object of this research.Material and methods. There research comprised 307 teachers from 37 schools of different types. All teachers were from the Opole Province and teaching different subjects. A diagnostic survey, using the author’s questionnaire, was chosen as the method of research.Results. The research showed that the examined teachers could see the link between physical education and health education and they recognized the significant role of educators in the process of shaping a healthy lifestyle. In the opinion of the researched group the teachers of biology and physical education are best prepared to be the leaders of school health education – most often the biology teachers, in the second place – physical education teachers. As many as 30% of the respondents do not see the leader of health education in their school. It is a worrying situation especially when the Ministry of Education made the physical education teacher responsible for this task.Conclusions. Making changes in education system of future teachers of physical education and training for currently working teachers – towards gaining leadership of health education competence, is urgently needed.